Investigation Interoperability Problems in Pharmacy Automation: A Case Study in Saudi Arabia - Binobaid, Saleh; Fan, Ip-Shing; Almeziny, M. (Elsevier, 2016)
The aim of this case study is to investigate the nature of interoperability problems in hospital systems automation. One of the advanced healthcare providers in Saudi Arabia is the host of the study. The interaction between the pharmacy system and automated medication dispensing cabinets is the focus of the case system. The research method is a detailed case study where multiple data collection methods are used. The modelling of the processes of inpatient pharmacy systems is presented using Business Process Model Notation. The data collected is analysed to study the different interoperability problems. This paper presents a framework that classifies health informatics interoperability implementation problems into technical, semantic, organisational levels. The detailed study of the interoperability problems in this case illustrates the challenges to the adoption of health information system automation which could help other healthcare organisations in their system automation projects.
Keywords: Electronic Health Record; Hospital information systems; interoperability problems; Information Modelling; Automation